Happiness or Quality of Life? Or Both? - Murgaš, František; Petrovič, František; Maturkanič, Patrik; Kralik, Roman (Journal of Education Culture and Society, 2022)
Aim. The aim of the article is to look for an answer to the question of whether it is worthwhile to deal only with happiness and to leave the exploration of quality of life as something which is not viable, or if it makes sense to deal with both phenomena. If so, what is the relationship between them? At the same time, we ask ourselves whether happiness and quality of life are perceived equally by people and are therefore interchangeable. Results. The answer is also confirmed by measuring the number of published articles monitored in the Web of Science. The quantification of happiness and quality of life implies that their correlation is high but not so high that they can be identified as the same. At the same time, if happiness and quality of life are different phenomena, it makes sense to deal with both. Method. The research was conducted using the face-to-face interview method. Conclusion. Happiness and quality of life, in terms of attention given to them by researchers, are quite different. We think mistakenly that they are the same on account of the preponderance of impression given to happiness in public space.